1990
DOI: 10.1161/01.cir.81.5.1488
|View full text |Cite
|
Sign up to set email alerts
|

Relation of pulmonary vein to mitral flow velocities by transesophageal Doppler echocardiography. Effect of different loading conditions.

Abstract: It has previously been demonstrated that predictable changes occur in mitral flow velocities under different loading conditions. The purpose of this study was to relate changes in pulmonary venous and mitral flow velocities during different loading conditions as assessed by transesophageal echocardiography in the operating room. Nineteen patients had measurements of hemodynamics, that is, mitral and pulmonary vein flow velocities during the control situation, a decrease in preload by administration of nitrogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
161
3
6

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(184 citation statements)
references
References 41 publications
14
161
3
6
Order By: Relevance
“…Systolic forward flow is often biphasic with S1 related to atrial relaxation and LA pressure while S2 is related to stroke volume and propagation in the arterial tree 44 , 45 (S2 is used to derive S/D ratio). D velocity is influenced by LV filling and compliance and changes parallel to mitral E velocity 46 . AR velocity and duration are affected by LV late diastolic pressures, atrial preload and LA contractility 47 .…”
Section: Pulmonary Venous Flow Patternsmentioning
confidence: 99%
“…Systolic forward flow is often biphasic with S1 related to atrial relaxation and LA pressure while S2 is related to stroke volume and propagation in the arterial tree 44 , 45 (S2 is used to derive S/D ratio). D velocity is influenced by LV filling and compliance and changes parallel to mitral E velocity 46 . AR velocity and duration are affected by LV late diastolic pressures, atrial preload and LA contractility 47 .…”
Section: Pulmonary Venous Flow Patternsmentioning
confidence: 99%
“…However, several studies have investigated the relationship between PCWP and TEE-derived Doppler indices of pulmonic vein flow in patients receiving mechanical ventilation. [9][10][11] Kuecherer et al, 10 in 42 mechanically ventilated patients undergoing cardiovascular surgery, showed that Doppler TEE indices of pulmonic vein flow correlated with PCWP. Similarly, Hofmann et al, 11 in 32 mechanically ventilated patients undergoing cardiac surgery, demonstrated a significant correlation between mean left atrial pressure and pulmonary venous peak systolic to peak diastolic velocity ratio.…”
Section: Comparison With Prior Studiesmentioning
confidence: 99%
“…Studies of diastolic function in adults using M-mode and Doppler echocardiography have shown the usefulness of unidimensional assessment of left atrial dynamics (6), atrioventricular (7)(8)(9) and pulmonary vein flow analysis (10)(11)(12)(13)(14) and, more recently, of tissue Doppler of atrioventricular rings and ventricular septum (15).…”
Section: Introductionmentioning
confidence: 99%